Validation of fast Monte Carlo dose calculation in small animal radiotherapy with EBT3 radiochromic films. (7th April 2016) - Noblet, C; Chiavassa, S; Smekens, F; Sarrut, D; Passal, V; Suhard, J; Lisbona, A; Paris, F; Delpon, G
Abstract: In preclinical studies, the absorbed dose calculation accuracy in small animals is fundamental to reliably investigate and understand observed biological effects. This work investigated the use of the split exponential track length estimator (seTLE), a new kerma based Monte Carlo dose calculation method for preclinical radiotherapy using a small animal precision micro irradiator, the X-RAD 225Cx. Monte Carlo modelling of the irradiator with GATE/GEANT4 was extensively evaluated by comparing measurements and simulations for half-value layer, percent depth dose, off-axis profiles and output factors in water and water-equivalent material for seven circular fields, from 20 mm down to 1 mm in diameter. Simulated and measured dose distributions in cylinders of water obtained for a 360° arc were also compared using dose, distance-to-agreement and gamma-index maps. Simulations and measurements agreed within 3% for all static beam configurations, with uncertainties estimated to 1% for the simulation and 3% for the measurements. Distance-to-agreement accuracy was better to 0.14 mm. For the arc irradiations, gamma-index maps of 2D dose distributions showed that the success rate was higher than 98%, except for the 0.1 cm collimator (92%). Using the seTLE method, MC simulations compute 3D dose distributions within minutes for realistic beam configurations with a clinically acceptable accuracy for beam diameter as small as 1 mm.